DISPENSASI KAWIN DAN PERLINDUNGAN ANAK: (Kritik MaqÃ„ÂÃ¡Â¹Â£id Terhadap Hukum Keluarga Islam Kontemporer) - Saini Saini (Program Studi Hukum Keluarga Islam, Fakultas Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
The phenomenon of marriage dispensation following national legal reform has shown a significant increase and raised controversy over the effectiveness of child protection within the framework of Islamic family law. Although Law No. 16 of 2019 established the minimum legal age for marriage as a preventive measure against child marriage, the enforcement of dispensations through Article 7(2) paradoxically creates a legal loophole that contradicts the lawÃ¢â‚¬â„¢s protective intent. This study focuses on a normative critique of marriage dispensation from the perspective of maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«Ã¢â‚¬Ëœah, examining to what extent contemporary Islamic family law remains responsive to the principles of Ã¡Â¸Â¥ifÃ¡Âºâ€œ al-nafs (protection of life) and Ã¡Â¸Â¥ifÃ¡Âºâ€œ al-nasl (protection of lineage). The research adopts a qualitative approach based on library research, with data collected from classical and contemporary legal texts, including works on maqÃ„ÂÃ¡Â¹Â£id, Islamic jurisprudence, and national legal documents. Content analysis was employed to reduce and categorize the data thematically. The findings reveal that dispensations granted without grounding in substantive maÃ¡Â¹Â£laÃ¡Â¸Â¥ah contradict the foundational principles of maqÃ„ÂÃ¡Â¹Â£id and tend to reproduce structural inequalities, particularly against young girls. The study concludes that maqÃ„ÂÃ¡Â¹Â£id al-sharÃ„Â«Ã¢â‚¬Ëœah must be repositioned as an epistemic framework for reformulating Islamic family law to enhance its commitment to justice and child protection. This research underscores the need for ethical and contextual legal reconstruction to avoid legalistic bias that harms vulnerable groups.